Assessing Canada's position in world trade - the statistical dimension - Purdue, R. (Statistics Canada OttawaCA, 1991)
Study covers the period 1970 to 1990. Provides a broad overview of global trade patterns; a national perspective reflecting some of the more salient characteristics of Canadian trade; and a microeconomic perspective providing highlights for specific industries.